Developing environmental flows for the Baleh River – hydrological and geomorphological processes in the Baleh catchment prior to damming - Chong, Xin Yi (2023)
Dams have been built in many parts of the world since the earliest human civilizations, but currently there is a significant program of dam building underway in the tropics. Despite general awareness of the likely detrimental impacts of dams, the limited number of empirical tropical studies means that specific effects of dams on these important but imperilled ecosystems are hard to predict. Although the Functional Flows (FFs) concept is now prominent in the scientific and river management literature, it has been applied only to some very specific cases in tropical areas to guide dam operation (e.g. to support periodic flooding of floodplain areas). In these and many other cases, FFs have been applied retrospectively, to design operational flows for existing dams. The work presented in this thesis concerns development of flow recommendations prior to the construction of a large tropical hydropower dam on Baleh River, Sarawak. Specific objectives of the thesis are to: (i) develop a full statistical understanding of the natural hydrological regime of Baleh River, (ii) identify critical habitat forming discharges (those responsible for coarse sediment entrainment and transport) and relations between discharge magnitude and hydraulic habitat heterogeneity, (iii) to assess the impact of the dam and other land use changes on sediment connectivity, and (iv) provide specific recommendations for dam operation to support sediment entrainment and maintenance of habitat heterogeneity, and for management of lake levels to limit changes in connectivity.